The Effect of Health Education using Animated Videos on Elementary School Girls' Behavior in Facing Menarche - Vivi Wirmalinda; Lili Fajria; Mahathir Mahathir (Indonesian Journal of Global Health Research, 2024)
The behavior of elementary school students in receiving menarche depends on several things, including social support and the availability of information. To carry out a learning method, it is necessary to have media that can support or channel the information conveyed through appropriate learning media. Learning media is a means of conveying information about lessons that can arouse students' enthusiasm for learning, thereby encouraging students to learn independently. Objective This research is to determine the effect of health education using animated videos on the behavior of elementary school students in facing menarche in West Pasaman District. The research was conducted in July 2024. The type of research was Quasi Experimental with a One-Group Pret-Post Test design. The population covered in the research were female students in West Pasaman District as many as 68 samples using total sampling technique. The research instrument used a questionnaire (rhitung > rtabel and alpha cronbach > 0,6). Univariate data analysis was presented in the form of a frequency distribution and bivariate analysis used the Wilcoxon test, data processing used the computerized SPSS program IBM version 25.0. The results of the research show that there is an effect of health education using animated videos on knowledge. This research aims to see the effect of health education using animated videos on the knowledge and attitudes of elementary school students in facing menarche. The conclusion is that there is an influence of health education using animated videos on the behavior of elementary school students in facing menarche.